Automotive vibration and noise control using smart materials: a state of art and challenges. (1st August 2014) - Kumbhar, S.; Maji, Subhasis; Kumar, Bimlesh
Abstract : In the past several years, there has been increased market place awareness of noise, vibration, and harshness performance in automobiles. The differentiation between the quality and reliability levels of automobiles has become less pronounced and, as a result, manufacturers have had to demonstrate superiority by focusing on NVH concerns. The automotive industry is currently spending millions of dollars on NVH work to develop new materials and damping techniques so that the damping treatments are lighter, cheaper and more effective. Some of the methods used to control noise, vibration and harshness includes the use of different carpeting treatments, the addition of rubber or asphalt material to car panels, gap sealant, and the injection of expandable foam into body panels. The aim of this study is to explore the feasibility of smart damping materials such as magnetorheological elastomers (MRE), piezoelectric materials, with its basic properties, for augmenting and improving the performance benefits of damping materials. This study also evaluates the noise and vibration benefits of smart damping materials as compared to conventional damping treatments.